Genome-wide C-SWAT library for high-throughput yeast genome tagging - Meurer, Matthias; Duan, Yuanqiang; Sass, Ehud; Kats, Ilia; Herbst, Konrad; Buchmuller, Benjamin; Dederer, Verena; Huber, Florian; Kirrmaier, Daniel; Štefl, Martin; Van Laer, Koen; Dick, Tobias P.; et al. (Nature methods, 2018)
Here we describe a C-SWAT library for high-throughput tagging of Saccharomyces cerevisiae open reading frames (ORFs). In 5,661 strains, we inserted an acceptor module after each ORF that can be efficiently replaced with tags or regulatory elements. We validated the library with targeted sequencing and tagged the proteome with bright fluorescent proteins to quantify the effect of heterologous transcription terminators on protein expression and to localize previously undetected proteins.
Gesehen am 07.04.2020